Effectiveness of Transversus Abdominis Plane Block as part of a Multimodal Analgesia to Reduce Opioid Consumption among Total Abdominal Hysterectomy Patients: A Randomized Control Trial - Haider, Md Ali; Begum, Rabeya; Islam, Md Sirajul; Islam, Md Nurul; Mondal, Subrata Kumar; Hossain, Md Gishan; Iqbal, Md Jahid (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Background:Generally patients after total abdominal hysterectomy have suffered from moderate tosevere postoperative pain. Multimodal approach are using to reduce this pain. Objective:The purpose of the present study was to observe the effectiveness of transversus abdominisplane block as part of amultimodal analgesia to reduce opioid consumption among total hysterectomypatients. Methodology:This randomized control trial was conducted in Department of Anaesthesia, Analgesia,Palliative and Intensive Care Medicine of Dhaka Medical College and Hospital, Dhaka, Bangladeshfrom March 2016 to September 2018 for a period two years and six months. Women planned for anelective total abdominal hysterectomy under general anesthesia were selected as study population.Participants were selected and randomly divided into two groups designed as group I and group II.Patient of both group were given general anesthesia. Group I patient received 20 ml 0.25% bupivacaineand group II patient received 20 ml normal saline as placebo. Then dressing was done. The TAP blockwas performed after taking all aseptic precaution in the flank palpated between the 12th rib (Costalmargin) and the iliac crest. After confirmation of correct position, 20 ml 0.25% bupivacaine was given togroup I patient and 20 ml normal saline was given to group II patient within the fascial layer whichwas confirmed by ultrasound. Result:A total number of 40 patients were recruited for this study and were equally divided into twogroups. Thus 20 patients were in the group I and the rest 20 patients were in group II. The mean age ofgroup I were 53.08 ±4.25 and group II were 51.5±4.97 (p= 0.286).In this study 5(25.0%) patients hadnausea in group I and 8(40.0%) in group II, 3(15%) patients had vomiting in group I and 4(20.0%) ingroup II (p>0.05). The mean first analgesic demand was 8.39±1.85 hours in group I and 1.59±0.21 hoursin Group II (p=0.001).The mean total morphine consumption was 14.78±3.56 in group I and 26.30±5.9in group II (p<0.05). Conclusion:TAP block effectively reduced the total postoperative morphine consumption. JBSA 2020; 33(1): 16-21